Noodle boy - Herras, Paolo; Pascual, Tepai (Meganon Comics Publishing House, 2014)
"Noodle boy is the quirky love story of a failed head chef Ayumi, and Carlo, a ramen-loving cosplayer. with three pretty maids by her side, a maid cafe she must manage, and a kitten she picks up from the street, fall in love at first taste with this fun and funny love story." -- Provided by publisher